Musikforlaget Wilhelm Hansens Arkiv på Erhvervsarkivet – en kilde til dansk musikhistorie - Foltmann, Niels Bo; Hauge, Peter (Danish Yearbook of Musicology, 1997)
The Music Publisher Wilhelm Hansen’s Archive at „Erhvervsarkivet“ – a Source to Danish Music History In connection with the sale of the music publishers Wilhelm Hansen in 1988, part of the company’s archive was transferred to „Erhvervsarkivet“ in Århus. The article presents this material which mainly covers the period from c.1895 to c.1940 with a closer examination of four important sources: ledgers for private accounts, journals containing catalogue numbers, the so-called Lagerbog A (store book A), and accounts concerning concerts. Finally, a preliminary registration is presented.